2y - 5 + 3y = 4 - (y + 2)
5y - 5 = 4 - y - 2
5y - 5 = 2 - y
5y - 5 + y = 2 - y + y
6y - 5 = 2
6y - 5 + 5 = 2 + 5
6y = 7
6y / 6 = 7 / 6
y = 7 / 6
y = 1 1/6
- - - - - - - - - - - -s-
2007-05-13 07:52:10
·
answer #1
·
answered by SAMUEL D 7
·
1⤊
0⤋
2y - 5 + 3y = 4 - (y+2)
First, factor the negative sign.
2y - 5 + 3y = 4 - y - 2
Second, combine like terms on both sides of the equation.
5y - 5 = 2 - y
Next, move all variable terms to one side of the equation, and all other terms to the other side of the equation.
6y = 7
Finally, isolate the variable by dividing each side y the coefficient (in this case, the 2 in front of the y)
y = 7/6
To check your answer, substitute this number into the original equation:
2(7/6) - 5 + 3(7/6) = 4 - (7/6 + 2)
14/6 - 30/6 + 21/6 = 4 - (7/6 + 12/6)
5/6 = 24/6 - 19/6
5/6 = 5/6
Hope this helps!
2007-05-13 07:37:11
·
answer #2
·
answered by allstargurl522 3
·
0⤊
1⤋
Solve the "y" variable in the equation.
2y - 5 + 3y = 4 - (y+2)
2y + 3y - 5 = 4 - y - 2
5y - 5 = 2 - y
First: add "y" to both sides (when you move a term to the opposite side).
5y - 5 + y = 2 - y + y
5y + y - 5 = 2
6y - 5 = 2
Sec: add 5 to both sides.
6y - 5 + 5 = 2 + 5
6y = 2 + 5
6y = 7
Third: divide both sides by 6.
6y/6 = 7/6
y = 7/6
2007-05-13 07:21:44
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
1⤊
1⤋
permit's try: 40 5-[4-2y-4(y+7)]= -4(a million+3y)-[4-3(y+2)-2(2y-5)] dispensing: 40 5-[4-2y-4y-28)] = -4-12y -[4-3y - 6 - 4y +10] 40 5-4+2y+4y+28 = -4 - 12y -4 +3y +6 +4y-10 sixty 9 + 6y = -5y -12 11y = -sixty 9-12 11y = -80 one it truly is nevertheless a fragment,,hmm..too undesirable.. y = -80 one/eleven
2016-12-17 11:35:04
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
2y - 5 + 3y = 4 - (y + 2)
2y - 5 + 3y = 4 - y - 2
(distribute the - sign)
5y - 5 = 4 - y - 2
(add the two y terms on the left)
5y - 5 = 2 - y
(add the two constant terms on the right)
6y - 5 = 2
(add y to both sides, in order to get rid of y terms on the left)
6y = 7
(add 5 to both sides, in order to get rid of constant terms on the right)
y = 7/6 = 1.16666...
(divide)
2007-05-13 07:23:38
·
answer #5
·
answered by cantorset 2
·
0⤊
1⤋
first of all simplify this equation by adding the y's and the simple numbers:
5y-5 = 4 - y -2
5y-5 = 2 -y
now get the y in the right side and put it in the left side dont forget that their signs change when they get from one side to the other.
5y + y = 5 +2
6y = 7
y =7/6
2007-05-13 07:28:15
·
answer #6
·
answered by kamil n 1
·
0⤊
1⤋
basically, shift all the coefficients of y to one side, and the rest to the other side so you get
2y +3y + y = 4 +5 -2
so you get 6y = 7
then y = 7/6
2007-05-13 07:29:12
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋
y=13
2007-05-13 07:19:38
·
answer #8
·
answered by someone 2
·
0⤊
3⤋
Shankar is right, its 7/6 (or 1 1/6)
2007-05-13 07:24:48
·
answer #9
·
answered by magnificientred 2
·
0⤊
1⤋
it simplifies to 6y=7
or y = 7/6
2007-05-13 07:16:21
·
answer #10
·
answered by shankar 2
·
0⤊
2⤋